A highly efficient and magnetically retrievable functionalized nano-adsorbent for ultrasonication assisted rapid and selective extraction of Pd2+ ions from water samples1. Issue 54 (13th June 2015) - Sharma, R. K.; Kumar, Harish; Kumar, Anil
<x xml:space="preserve">Abstract</x> A novel and highly efficient magnetic core shell based nanoadsorbent has been fabricated and applied for the extraction of Pd2+ ions.